(3YeGQI eOGNd GdcfGFS GdeSjMjI ai GdbGgQI h GdhLg GdHMQi NdGd GdYUQ GdESdGei (B: s (3OQGSI BKGQjI eYeGQjI h afjI (B/ s - (3efGd eMehO Ydi eMeO YGThQs; (3CMeO QLH eMeO Ydi QRb (B: s; (3eMeO MeRI ESeGYjd GdMOGO (B: s ((3GdbGgQI (B: s (3efGd eMehO Ydi eMeO YGThQ (B: s, 2020)
(3JJfGhd GdQSGdI YeGQI eOGNd GdcfGFS GdeSjMjI ai GdbGgQI h GdhLg GdHMQi NdGd GdYUQ GdESdGei(B: (3h JJVef GdQSGdI GdebOeI(B: (3h GdJi JhVM CSHGH ENJjGQ GdehVhY h CgejJg(B: (3h bGFeI HCge GdcfGFS GdehLhOI HGdbGgQI h GdhLg GdHMQi NdGd GdYUQ GdESdGei ai GdaJQI efP GdaJM GdYQHi GdESdGei deUQ h MJi fgGjI YUQ CSQI eMeO Ydi(B: (3h GdUYhHGJ GdJi hGLgJ GdHMK(B: (3h GdOQGSGJ GdSGHbI h Cge GdeQGLY GdJi CYJeOJ YdjgG ai HMKi(B. (3GdHGH GdChd(B: (3GdOQGSI GdhUajI deOGNd GdcfGFS GdeSjMjI GdHGbjI HeMGaXI GdbGgQI h eMGaXGJ GdhLg GdHMQi(B: (3h bO bSe Edi aUdjf(B: (3GdaUd GdChd(B: (3OQGSI hUajI dHYV eOGNd GdcfGFS GdeSjMjI GdHGbjI HeMGaXI GdbGgQI(B: (3h jTJed Ydi CQHYI eHGMK(B: (3GdeHMK GdChd(B: (3eOGNd cfGFS GdCbHGW GdCQKhPcS GdHGbjI ai GdbGgQI(B: (3GdeHMK GdKGfi(B: (3eOGNd cfGFS GdCbHGW GdcGKhdjc GdHGbjI ai GdbGgQI(B: (3GdeHMK GdKGdK(B: (3eOGNd cfGFS GdCbHGW GdEfLjdjjf GdHGbjI ai GdbGgQI(B: (3GdeHMK GdQGHY(B: (3eOGNd cfGFS GdLGdjGJ GdCLfHjI GdHGbjI ai GdbGgQI(B: (3GdaUd GdKGfi(B: (3OQGSI hUajI dHYV eOGNd GdcfGFS GdHGbjI HeMGaXGJ GdhLg GdHMQi(B: (3jTJed Ydi eHMKjf(B: (3GdeHMK GdChd(B: (3OQGSI hUajI deOGNd cfGFS GdCbHGW GdHGbjI HeMGaXGJ GdhLg GdHMQi(B: (3GdeHMK GdKGfi(B: (3OQGSI hUajI deOGNd cfGFS GdLGdjGJ GdCLfHjI GdHGbjI HeMGaXGJ GdhLg GdHMQi(B. (3GdHGH GdKGfi(B: (3GdOQGSI GdJMdjdjI deOGNd GdcfGFS GdeSjMjI ai GdbGgQI h GdhLg GdHMQi NdGd GdYUQ GdESdGei(B: (3h bO bSe Edi NeSI aUhd(B: (3GdaUd GdChd(B: (3ehGO GdHfGA GdeSJNOeI ai YeGQI hRNQaI eOGNd GdcfGFS GdeSjMjI ai GdbGgQI hGdhLg GdHMQi NdGd GdYUQ GdESdGeis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdBKGQ GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdYUQ GdESdGeis; (3GdYeGQIs; (3GdeONds